"Time for Tony the Turtle": Experiences with the use of a hand puppet in a program for young children in domestic violence shelters. (September 2021) - van der Hoeven, Mara L.; Widdershoven, Guy A.M.; van Duin, Esther M.; Hein, Irma M.; Lindauer, Ramón J.L.
Highlights: The use of a hand puppet in a program for children in DV shelters seems beneficial. A hand puppet becomes a trusted figure for children in DV shelters. Children can use the puppet to project their own problems onto. Children can advise and question the puppet on sensitive topics. Abstract: A support program 'Time for Tony the Turtle' has been developed for young children residing in Dutch domestic violence (DV) shelters. With hand puppet 'Tony the Turtle', the program aims to develop self-regulation skills for children, while increasing the sense of safety and addressing children in a personal and playful way. As the use of the puppet is a distinct aspect of the program, this study aims to explore the experiences of children, mothers, and professionals with a hand puppet in three Dutch organizations providing shelter services. We conducted in-depth interviews with 11 children, 15 mothers, and 18 professionals involved in the program. We used thematic analysis for interpretation. We derived three themes from the interviews with the interviewees: 'Tony is nice and funny', 'Tony is just like us', and 'Tony invites us to ask questions and give advice on sensitive topics'. Overall, the use of a hand puppet in DV shelters seems beneficial for children living in DV shelters. It offers a trusted figure who experienced similar things. Children can use the puppet to project their own problems onto and to find solutions for their problems and concerns, by advising the puppet and asking it questions.